Psychological Distress Among Social Media Addicts of Pakistan (Journal of Asian Development Studies, 2025)
There is substantial literature on psychological distress—specifically depression and anxiety— among social media addicts in Pakistan. However, studies exploring the association between these variables within this group are limited, particularly among young adults aged 20 to 30. Therefore, this study addresses this gap and provides practical implications for mental health awareness and intervention. A cross-sectional correlational research design was employed to examine the relationship between depression and anxiety among young adults. Data were collected using a purposive sampling technique from 150 university students aged 20 to 30 years (M = 24.61, SD = 2.68) who scored 24 or higher on the Bergen Social Media Addiction Scale (BSMAS), indicating the cutoff score for classification as social media addicts. The Beck Depression Inventory–Second Edition (BDI-II) and the Beck Anxiety Inventory (BAI) were used to measure the study variables. It was hypothesized that anxiety and depression would be significantly associated with each other. The results supported this hypothesis, revealing a significant positive correlation between depression and anxiety among social media addicts. This study offers valuable implications, such as encouraging proactive roles for parents and government authorities and promoting mental health awareness through professionals and media channels.